Biofortification of zinc in sorghum grown in rainfed black soil (Typic Chromusterts) - Baskar, K; Vigneshwaran, R; Manoharan, S; Manikandan, M; Manikandan, K (Plant Science Today, 2025)
Zinc (Zn) is a crucial micronutrient for crop growth and enzymatic regulations. The present study was formulated to reveal the effect of organic fortified Zn composite on the development and yield of sorghum. The field screening experiment was laid out in a factorial arrangement of Randomized Block Design (FRBD) with three replications. The treatments consisted of factor 1 were four microbial inoculants viz. M1: Plant Growth-Promoting Rhizobacteria (PGPR), M2: Zinc-Solubilizing Bacteria (ZSB), M3: Vesicular-Arbuscular Mycorrhiza (VAM), M4: Control, 100 % recommended NPK at 40:20:0 kg ha-1 with Zn was applied as a common dose to all treatment plots and 20 sorghum genotypes considered as another factor 2. Among the genotypes, the variety K12 recorded the highest Dry Matter Production (DMP) (5069 kg ha-1) at vegetative and other genotypes like TKSV 1036, PYT CO 30, TKSV 1315 and TKSV 1307 recorded DMP of 4950, 4946, 4921 and 4910 kg ha-1 were found efficient and responsive. Among the screened genotypes K12 and TKSV 1036 were found to be responsive genotypes. Further, various zinc levels of field experiments II were conducted with the efficient and responsive genotypes K12 and TKSV 1036, which were studied by imposing fifteen treatments in a split plot design and replicated thrice. Higher mean Zn uptake of 10.4, 59.9 and 41.9 g ha-1 was also recorded by Zinc Solubilising Bacteria (M1) at vegetative, flowering and harvest respectively. The highest grain yield of 4334 kg ha-1 was registered by S15, which was comparable with S14 (4291 kg ha-1). The highest grain zinc uptake of 48.42 g ha-1 was recorded with the application of S9 + Zn-EOM at 50 kg ha-1. Farmers in saline soil can adopt this integrated zinc nutrient management to enrich zinc and enhance the growth and yield of sorghum in potentially zinc-deficient soil.